Supplemental Wheat Germ Activates the STAT3-Reg3 Pathway in the Gut and Attenuates the Lipopolysaccharide Binding Protein Gene in the Adipose Tissue of Mice Fed a Western Diet. (29th May 2020) - Alake, Sanmi; Ojo, Babajide; Kaur, Amritpal; Wong, Siau Yen; Keirns, Bryant; Ritchey, Jerry; Chowanadisai, Winyoo; Lucas, Edralin; Clarke, Stephen; Smith, Brenda; Lucas, Edralin
Abstract: Objectives: This study investigated the effects of wheat germ (WG) on gut antimicrobial peptides (AMPs, i.e., regenerating islet-derived protein [Reg] 3 g and Reg3b) in the jejunum and its potential to inhibit nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) activation and immune cell infiltration in the visceral adipose tissue (VAT) of mice fed a control or a western diet (i.e., high fat and high sucrose, HFS). Methods: Six-wk-old male C57BL/6 mice were randomly assigned to four groups ( n = 12/group), and fed a control (C, 10% kcal fat, 10% kcal sucrose) or HFS (45% kcal fat, 26% kcal sucrose) diet with or without 10% WG (wt/wt) for 12 wks. Metabolic parameters were quantified in the serum. Phosphorylation of STAT3 in the jejunum and NF-kB activation in the VAT were assessed by immunoblotting. Gut antimicrobial peptide genes, and macrophage and inflammatory markers were measured by qPCR. Results: After 12 wks of dietary treatment, WG significantly improved hyperglycemia, fasting insulin, and homeostatic model assessment of IR (HOMA-IR) by at least 17% ( P ≤ 0.0034) in HFS-fed mice. Protein expression of the pore-forming claudin-2 was elevated in the jejunum of HFS-fed mice (≥101%; P = 0.0016). Supplemental WG upregulated Il-10 and Il-22 genes in the jejunum (≥116%; P ≤ 0.035). The HFS + WG group had a 15-fold increase ( P = 0.0012) in pSTAT3 compared to the HFS group in the jejunum. Consequently, the mRNA expression of Reg3b and Reg3g were significantly upregulated in the jejunum by WG supplementation (≥42%; P ≤ 0.043). In the VAT, the HFS group had greater NF-kBp65 phosphorylation compared to C, while HFS + WG group suppressed this to the level of C (–38%; P = 0.014). In addition, VAT Il-6 and Lbp genes were downregulated in the HFS + WG group compared to HFS ( P ≤ 0.0032). Macrophage-related genes, F4/80, Cd11c, and iNos, were repressed (≥−28%; P ≤ 0.048) in the VAT of WG-supplemented mice. Conclusions: The stimulatory effects of WG on signal transducer and activator of transcription (STAT3) and AMPs in the gut may be vital to reduce the burden of antigen translocation that could initiate adipose tissue inflammation and contribute to obesity-induced IR. Funding Sources: This study was funded by Oklahoma Agriculture Experiment Station (project # OKL02993) and by the Oklahoma State University College of Human Sciences.